Differences in proximal and intimacy-related defense mechanisms among patients with cancer in different psychological stages of dying - Zhou, Jia; Li, Mengxiang; Dong, Jiarui; Shi, Hui; Shi, Meihong (Frontiers in Psychology, 2024)
Purpose This study measured three of the psychological stages of dying in patients with cancer and explored the differences in proximal and intimacy-related defense mechanisms at each stage. Patients and methods A total of 220 cancer patients were recruited for this study; 168 patients met the inclusion criteria and were included in the data analysis. The participants were divided into three groups using the “Death Attitudes Questionnaire Revised” (1994) and then completed the Death-Thought Accessibility Test, Self-Control Questionnaire, Rumination Reflection Questionnaire, Attachment Type Test, Intimacy Test, External Control Test, and Positive and Negative Affect Scale. Results In the death avoidance stage, which represents a defense stage without cognitive processes, patients are in an irrational state with the highest level of self-control and the lowest level of external control; they tend to prefer close relationships with many people while experiencing high levels of fear and depression. In the bargaining stage, which represents a biased cognitive defense stage, the level of rationality increases, the level of fear and depression decreases, and patients tend to prefer relationships with many people that do not involve intimacy. In the neutral death acceptance stage, which represents a defense stage without cognitive bias, self-control is lowest, external control is highest, patients tend to prefer intimate relationships with a few people, and experience the lowest levels of fear and depression. Conclusion Three psychological stages of death exist in cancer patients, with differences in proximal and intimacy-related defense mechanisms in each stage. The findings have theoretical and practical implications for psychological interventions for cancer patients.